Potential Anxiolytic Impact of Mercurialis annua Extract in Mice Following Acute Therapy - Zouhra Doukkali; Abduladeem G.M. Al-Selwi (Pharmaceutical Science: New Insights and Developments Vol. 3, 2025)
Current therapeutic options for anxiety are often associated with a wide variety of significant side effects. The traditional use of plant extracts in healthcare highlights an important source for discovering new pharmaceuticals. In Moroccan traditional medicine, Mercurialis annua is frequently recommended for alleviating anxiety. However, despite its widespread use, no studies have explored its potential neuropharmacological effects. In this study, we investigated the potential anxiolytic effects of M. annua extract following acute treatment in mice. The methanolic extract from the aerial parts of M. annua (at doses of 100, 200, or 400 mg/kg) was administered orally, and its anxiolytic effects were assessed using the hole-board test, the light–dark box test, and motor coordination using the rota-rod test. Diazepam (1 mg/kg) was used as the standard reference drug. The methanolic extract of M. annua at a dose of 100 mg/kg increased the time spent in the brightly lit chamber of the light/dark box and the number of transitions between compartments. Additionally, performance on the rota-rod test remained unaffected. In the hole-board test, the extract significantly enhanced head-dip counts. These findings support the anxiolytic activity of M. annua, aligning with its traditional medicinal use. Moreover, they suggest that M. annua may have a more favorable side-effect profile compared to diazepam.